The Study of Code Switching in “Algoritme Rasa” Novel - Marselina Helita Alus; I. G. B. Wahyu Nugraha Putra; Putu Devi Maharani (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2021)
Code switching occurs when the bilingual or multilingual people shift the code from one to another code in conversation. The aimed of this study is focused to analyse the types of code switching found in Algoritme Rasa Novel. Descriptive Qualitative method was applied in analysing the data. This study applied the theory Bilingualism by Poplack in Romaine (1995) to analysing the types of Code switching. Those are three types of Code Switching: Tag Switching, Inter-Sentential Switching, Intra-Sentential switching. The result of this study showed that all the three types of Code Switching were found on Algoritme Rasa Novel. The most dominant of the types of Code switching occurrence in Algoritme Rasa Novel is Intra-Sentential switching with 58 data meanwhile, Tag Switching be the lowest dominant data used by speaker with 23 data.